On the role of temperature in the triplet-fusion induced low-energy photon up-converted delayed luminescence of a solid state composite - Goudarzi, Hossein; Keivanidis, Panagiotis E. (My University, 2014)
Here we present a temperature dependent spectroscopic study of a solution-processed solid state photon up-converting composite. In our work we address the process of low-energy photon up-conversion at low temperatures in the previously studied blend film of the triplet photosensitizer (2,3,7,8,12,13,17,18-octaethyl-porphyrinato) platinum(II)) (PtOEP) mixed with the blue emitter 9,10-diphenylanthracene (DPA). It is found that, in respect to room temperature, at 100 K the spectral integral of the DPA up-converted emission is increased by a factor of two whereas the spectrally integrated PtOEP phosphorescence is increased by a factor of eight. Temperature-dependent PtOEP phosphorescence and DPA up-converted luminescence kinetics are also recorded.
Keywords: Energy migration; Light harvesting; Photon up-conversion; Spectral diffusion; Triplet fusion